Building Transformation Networks for Consistent Evolution of Interrelated Models - Klare, Heiko (The Karlsruhe Series on Software Design and Quality, 2022)
Complex software systems are described with multiple artifacts, such as code, design diagrams and others. Ensuring their consistency is crucial and can be automated with transformations for pairs of artifacts. We investigate how developers can combine independently developed and reusable transformations to networks that preserve consistency between more than two artifacts. We identify synchronization, compatibility and orchestration as central challenges, and we develop approaches to solve them.